The growth performance of broiler chicks fed with diets containing cottonseed meal supplemented with lysine - Azman, MA; Yilmaz, M (Ecole Nationale Veterinaire Toulouse, 2005)
The aim of this study was to investigate the effects of diets containing cottonseed meal (CSM) supplemented with lysine in substitution for soybean meal (SBM) on growth performance of broilers. A total of 300, 7-day-old broilers were randomly assigned to 3 groups. The chicks were fed with corn-soy based starter diets (control group) or fed with 20% CSM based diets supplemented with 1.5% or 3% lysine (experimental groups) during 15 days. Higher body weights were observed in group treated by CSM-1.5% lysine than in group treated by CSM-3% lysine (p < 0.01). But, no significant differences in body weight, daily body weight gains, daily feed intake, and in feed conversion ratios were found between experimental and control groups during the experimental period. In conclusion, this study indicates that CSM with adequate supplementation of lysine could be incorporated in broiler diets without reduction of growth performance.
Keywords: cottonseed meal; lysine; growth performance; broiler